Punicalagin Alleviates Oxidative Stress and Pathological Changes in Brain of Mice-Fed High Fat, High Fructose Diet: Life Sciences-Biochemistry for better diagnosis and therapy - Chandrasekaran Sathiya Priya; Ramachandran Vidhya; Kalivarathan Jagan; Carani Venkatraman Anuradha (International Journal of Life Science and Pharma Research, 2022)
The present study investigated to know whether the pomegranate polyphenol punicalagin (PU) can ameliorate oxidative stress and pathological alterations induced by a calorie rich diet comprised of fat and fructose. Male Swiss albino mice were fed normal pellet (Control) or high fat-high fructose diet (HFFD) for 60 days. PU (30 or 60 mg/kg bw) was administered orally for the last 15 days for both dietary groups. Measurement of TBARS, AOPP and FRAP in plasma, histopathology of liver and brain, assessment of oxidative damage in brain tissues, and blood brain barrier function were carried out. HFFD mice showed an increase in the levels of TBARS and AOPP, and a decline in FRAP. PU administration to HFFD mice reduced the levels of TBARS and AOPP and improved FRAP significantly. Histopathology results showed fatty changes and inflammatory infiltration in the liver of HFFD mice. Cortex and hippocampus of HFFD mice confirmed the presence of degenerating neurons with shrunken cytoplasm and pyknotic nuclei. PU treatment caused significant hepato and neuroprotective effects, and among the two doses the high dose of PU (60 mg/kg) showed more pronounced effects than the low dose (30 mg/kg). The immunohistochemical localization of the markers of oxidative damage to proteins (3-NT), lipids (4-HNE) and DNA (8-OHG) was increased in brain tissues of HFFD mice and upon PU administration (60 mg/kg) the levels of these oxidative stress markers were significantly decreased. Our findings clearly suggest that PU can modulate oxidative stress and could be a potential candidate for treating neurodegenerative processes associated with calorie excess.